Asymmetries in the Magnetosheath Field Draping on Venus' Nightside. Issue 10 (25th October 2017) - Delva, M.; Volwerk, M.; Jarvinen, R.; Bertucci, C.
Abstract: Draping features of the interplanetary magnetic field around nonmagnetic bodies, especially Venus, have been studied in detail in numerical simulations and also from observations. Existing analytical and numerical work for nonperpendicular interplanetary magnetic field and solar wind velocity direction show a kink in the draped fieldlines in the near magnetosheath on the quasi‐parallel side of the bow shock. Here long‐term magnetic field data from the Venus Express mission (2006–2014) are analyzed in the near‐nightside region of the magnetosheath, searching for differences in the draping pattern between the quasi‐parallel and quasi‐perpendicular side of the shock. From these magnetometer (MAG) data, the kink in the fieldlines occurring only on the quasi‐parallel side is clearly identified from the change of sign in the field component parallel to the solar wind velocity. Furthermore, an asymmetry in the deflection of the out‐of‐plane field component due to the slipping of the fieldlines over the planetary obstacle is also found, which confirms predictions from numeral studies and from earlier work. Key Points: For oblique solar wind velocity and IMF direction, fieldline draping in the nightside magnetosheath is asymmetric with kink only on the quasi-parallel shock side Asymmetry not related to direction of motional electric field